2002
DOI: 10.1074/jbc.m203684200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the L116K Variant of CooA, the Heme-containing CO Sensor, Suggests the Presence of an Unusual Heme Ligand Resulting in Novel Activity

Abstract: CooA is the CO-sensing transcriptional activator from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…(It is unknown why the same I113D CooA variant accumulates poorly hemecontaining CooA in 1ϫ MOPS-buffered media anaerobically in the presence of CO.) Originally, we planned to purify a CooA variant with hydrophilic residues at position 116 as well, but we failed because such variants were unstable. Instability of heme-containing CooA variant at this position has been already reported (23). Fig.…”
Section: Weakening Thementioning
confidence: 81%
See 2 more Smart Citations
“…(It is unknown why the same I113D CooA variant accumulates poorly hemecontaining CooA in 1ϫ MOPS-buffered media anaerobically in the presence of CO.) Originally, we planned to purify a CooA variant with hydrophilic residues at position 116 as well, but we failed because such variants were unstable. Instability of heme-containing CooA variant at this position has been already reported (23). Fig.…”
Section: Weakening Thementioning
confidence: 81%
“…L116H CooA is intriguing because His could be a ligand in the Fe(II) form, as has strongly been suggested for Lys in L116K CooA (23). We previously showed that Lys ligation in this variant led to the unusually high activity of Fe(II) form and decrease of its activity upon CO binding (23). It is a reasonable hypothesis that His 116 ligation could be the origin for this phenotype in L116H CooA.…”
Section: Weakening Thementioning
confidence: 99%
See 1 more Smart Citation
“…This means that the heme must slide to the C-terminal side on the helix, and this view is consistent with the close proximity of the Leu 116 , Gly 117 , and Leu 120 triad to the CO-bound heme. Leu 116 is reported to be crucial for CooA activity, and the L116K mutant is active in both ferrous and CO-bound states (20). Leu 116 is close to the heme in our model (Fig.…”
Section: Inactive Ferrous Form-inmentioning
confidence: 88%
“…When Leu 116 is replaced by the heme-coordinating lysine residue, CooA is active both in the presence and absence of CO (20). The importance of the nearby Gly 117 to CooA activation has also been stressed (21).…”
mentioning
confidence: 99%